Factors Affecting Greenhouse Sweetpotato Slip Production. Issue 3 (4th May 2017) - Jiang, Chen; Pesic-VanEsbroeck, Zvezdana; Osborne, Jason A.; Schultheis, Jonathan R.
ABSTRACT: Sweetpotato certified seed producers rely on fast propagation of virus-indexed slip plants in the greenhouse to obtain transplants for the production of first generation of storage roots. Effective fertilization is important for greenhouse vegetative propagation, but relevant guidelines are rare. Greenhouse experiments were conducted in 2011 and 2012 using sweetpotato ( Ipomoea batatas (L.) Lam.) var. Covington, Beauregard, and Evangeline to evaluate effects of fertilizer rate on slip production. The most commonly used commercial fertilizer mix (20N–10P–20K) was applied at the rates 50, 100, 200, 300, 400 mg·L −1 of N. Plants were harvested nine times over the season in both years. Total nodes on vines and total slip fresh weight were determined. 'Evangeline' produced more nodes—that is, more plants—than 'Beauregard' and 'Covington', and 'Beauregard' produced the highest slip fresh weight, followed by 'Evangeline' and 'Covington'. Effect of fertilizer rate on vine node count was similar for early (harvests 1–3) and middle harvests (harvests 4–6) but impacted late harvests (harvests 7–9), where fertilizer rates from 100 to 300 mg·L −1 of N resulted in similar number of plant nodes, and 50 and 400 mg·L −1 of N reduced node count. Undesirable storage root formation in pots was favored by 50 mg·L −1 of N fertilizer rate, whereas fertilizer at or above 100 mg·L −1 of N inhibited them. 'Covington' produced the most storage roots. Fertilizer rate during slip production in the greenhouse did not affect transplant stand count in the field and subsequent field production of sweetpotato storage roots. The commercial fertilizer 20N-10P-20K should be applied from 100 to 200 mg·L −1 of N to produce the most slips and least storage roots in greenhouse pots.